Exercise Induces Different Molecular Responses in Trained and Untrained Human Muscle - Moberg, Marcus; Lindholm, Malene E; Reitzner, Stefan M; Ekblom, BjÖrn; Sundberg, Carl-Johan; Psilander, Niklas (Medicine and science in sports and exercise, 2020)
Human skeletal muscle is thought to have heightened sensitivity to exercise stimulus when it has been previously trained (i.e., it possesses "muscle memory"). We investigated whether basal and acute resistance exercise-induced gene expression and cell signaling events are influenced by previous strength training history. Accordingly, 19 training naïve women and men completed 10 wk of unilateral leg strength training, followed by 20 wk of detraining. Subsequently, an acute resistance exercise session was performed for both legs, with vastus lateralis biopsies taken at rest and 1 h after exercise in both legs (memory and control). The phosphorylation of AMPK and eEF2 was higher in the memory leg than that in the control leg at both time points. The postexercise phosphorylation of 4E-BP1 was higher in the memory leg than that in the control leg. The memory leg had lower basal mRNA levels of total PGC1α and, unlike the control leg, exhibited increases in PGC1α-ex1a transcripts after exercise. In the genes related to myogenesis (SETD3, MYOD1, and MYOG), mRNA levels differed between the memory and the untrained leg; these effects were evident primarily in the male subjects. Expression of the novel gene SPRYD7 was lower in the memory leg at rest and decreased after exercise only in the control leg, but SPRYD7 protein levels were higher in the memory leg. In conclusion, several key regulatory genes and proteins involved in muscular adaptations to resistance exercise are influenced by previous training history. Although the relevance and mechanistic explanation for these findings need further investigation, they support the view of a molecular muscle memory in response to training.